Apes in space: saving an imperilled orangutan population in Sumatra. - Gail Campbell-Smith; Miran Campbell-Smith; Ian Singleton; Matthew Linkie (PLoS ONE, 2011)
Deforestation rates in Sumatra are amongst the highest in the tropics. Lowland forests, which support the highest densities of orangutans, are particularly vulnerable to clearance and fragmentation because they are highly accessible. Consequently, many orangutans will, in the future, live in strictly or partially isolated populations. Whilst orangutans have been extensively studied in primary forests, their response to living in human-dominated landscapes remains poorly known, despite it being essential for their future management. Here, we focus on an isolated group of critically endangered Sumatran orangutans (Pongo abelii) that co-exist with farmers in a mixed agroforest system consisting of degraded natural forest, smallholder (predominantly rubber) farms and oil palm plantations. Over 24 months we conducted the first ever spatial assessment of orangutan habitat use in the human-transformed landscape of Batang Serangan, North Sumatra. From 1,204 independent crop-raiding incidents recorded, orangutans showed strong foraging preference for mixed farmland/degraded forest habitat over oil palm patches. The core home range areas of the eight adult orangutans encompassed only 14% of the available study area. Monthly home range sizes averaged 423 ha (±139, SD) for males, and 131 ± 46 ha for females, and were positively influenced by wild and cultivated fruit presence, and by crop consumption. The average daily distance travelled was similar for both adult males (868 m ± 350, SD) and females (866 m ± 195), but increased when orangutans raided crops. These findings show that orangutans can survive, demographically, in certain types of degraded landscapes, foraging on a mixture of crops and wild fruits. However, the poor quality habitat offered to orangutans by oil palm plantations, in terms of low food availability and as a barrier to female movements, is cause for concern since this is the land use type that is most rapidly replacing the preferred forest habitat across both Sumatran and Bornean orangutan ranges.